The Meloidogyne graminicola effector MgMO289 targets a novel copper metallochaperone to suppress immunity in rice. (11th May 2021) - Song, Handa; Lin, Borong; Huang, Qiuling; Sun, Longhua; Chen, Jiansong; Hu, Lili; Zhuo, Kan; Liao, Jinling
Abstract : A plant pathogenic nematode effector utilizes the host superoxide radical-scavenging system to decrease O2 − and suppress plant immunity. Abstract: Recent studies have reported that plant-parasitic nematodes facilitate their infection by suppressing plant immunity via effectors, but the inhibitory mechanisms remain poorly understood. This study found that a novel effector MgMO289 is exclusively expressed in the dorsal esophageal gland of Meloidogyne graminicola and is up-regulated at parasitic third-/fourth-stage juveniles. In planta silencing of MgMO289 substantially increased plant resistance to M. graminicola . Moreover, we found that MgMO289 interacts with a new rice copper metallochaperone heavy metal-associated plant protein 04 (OsHPP04), and that rice cytosolic COPPER/ZINC -SUPEROXIDE DISMUTASE 2 (cCu/Zn-SOD2) is the target of OsHPP04. Rice plants overexpressing OsHPP04 or MgMO289 exhibited an increased susceptibility to M. graminicola and a higher Cu/Zn-SOD activity, but lower O2 − content, when compared with wild-type plants. Meanwhile, immune response assays showed that MgMO289 could suppress host innate immunity. These findings reveal a novel pathway for a plant pathogen effector that utilizes the host O2 − -scavenging system to eliminate O2 − and suppress plant immunity.